PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS ANDROID UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA (Studi pada Siswa Kelas X Teknik Komputer dan Jaringan SMK N 2 Lahat) - Susi Oktarina; Bambang Sahono (UNIB Press, 2020)
Research on the development of an Android-based chemistry learning media to improve student achievement is developed using Appy Pie which is an online builder available on the internet. Appy Pie is a website that provides templates in making android applications. This chemical bond android application media contains five main features namely E-Material features, Video features, Quiz features, Forum Features, and About Us features. This development research was conducted in several stages, namely preliminary studies, prototype development, field testing, and dissemination and socialization. The population of the study was grade X students majoring in TKJ SMK N 2 Lahat. Data collection in this study uses observation, questionnaires, documentation and tests (pretest and posttest) using multiple choice questions of chemical bonding material. The stage of content assessment and media content from the media obtained an assessment with a very good category. The number of respondents in this study were 25 people in the experimental class and 25 people in the control class. The results of this development study indicate that: The use of android-based learning media in learning chemistry in class X TKJ SMKN 2 Lahat is good. There is a significant difference between the learning achievement of the control class and the experimental class.PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS ANDROID UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA(Studi pada Siswa Kelas X Teknik Komputer dan Jaringan SMK N 2 Lahat)